A dinâmica da dívida externa brasileira (1995-2012) - Dal Moro, Odirlei Fernando (2014)
The dynamics of the Brazilian external debt in the period 1995/1998, was important in enabling the success of the Real Plan. In the years that followed, the behavior of foreign debt towards closing the balance of payments was not as significant, though at times has favored. Accordingly, analyzes were performed aiming to show the behavior of gross debt and net external debt, always contrasting with the balances of the balance of payments. In the period 2003/2010, the external debt fell during the first term of President Lula, but resumed an upward trend in the second term. In the period 2007/2010, even with rising gross external debt, Brazil became creditor in foreign currency, because international reserves have expanded more than the gross external debt. In Dilma (2011-2012) government, gross external debt continued to grow along with the Brazilian credit abroad. The country has experienced and continues thus living a favorable phase of the external point of view, although the quality of international reserves and the associated risks are observation points For such purposes, comparative tables involving the Brazilian foreign debt, Gross Domestic Product, external accounts results and some external vulnerability indicators were used.